Structural properties of electrodeposited Cu-Ag alloys. (10th October 2017) - Bernasconi, Roberto; Hart, James L.; Lang, Andrew C.; Magagnin, Luca; Nobili, Luca; Taheri, Mitra L.
Abstract: Cu-Ag alloys are promising materials for electrical interconnections due to their combination of high conductivity and superior mechanical strength. In the present work, Cu-Ag alloys were electrodeposited from a cyanide-free electrolytic bath and different Ag percentages, ranging from 3 to 15 at.%, were obtained by controlling the deposition conditions. Electrochemical processes occurring during Cu-Ag deposition were investigated by means of cyclic voltammetry. Structural properties were examined by TEM and XRD and hardness was assessed by microindentation. TEM observations revealed the presence of nano-sized Ag precipitates at low Ag content, and the composition of the Cu-rich and Ag-rich phases in high-Ag alloys was deduced from XRD measurements. As-deposited alloys exhibited high hardness values and the contribution of solid-solution hardening was highlighted.